Enhanced uptake and anti-maturation effect of celastrol-loaded mannosylated liposomes on dendritic cells for psoriasis treatment - Long Xi; Zibei Lin; Fen Qiu; Shaokui Chen; Ping Li; Xin Chen; Zhenping Wang; Ying Zheng (Elsevier, 2022)
Psoriasis is an autoimmune skin disease in which dendritic cells (DCs) trigger the progression of psoriasis by complex interactions with keratinocytes and other immune cells. In the present study, we aimed to load celastrol, an anti-inflammatory ingredient isolated from Chinese herbs, on mannosylated liposomes to enhance DC uptake as well as to induce DC tolerance in an imiquimod-induced psoriasis-like mouse model. Mannose was grafted onto liposomes to target mannose receptors on DCs. The results demonstrated that compared with unmodified liposomes, DCs preferred to take up more fluorescence-labeled mannosylated liposomes. After loading celastrol into mannose-modified liposomes, they effectively inhibited the expression of maturation markers, including CD80, CD86 and MHC-II, on DCs both in vitro and in vivo. Additionally, after intradermal injection with a microneedle, celastrol-loaded mannose-modified liposomes (CEL-MAN-LPs) achieved a superior therapeutic effect compared with free drug and celastrol-loaded unmodified liposomes in the psoriasis mouse model in terms of the psoriasis area and severity index, histology evaluation, spleen weight, and expression of inflammatory cytokines. In conclusion, our results clearly revealed that CEL-MAN-LPs was an effective formulation for psoriasis treatment and suggested that this treatment has the potential to be applied to other inflammatory diseases triggered by activated DCs.